Polygenic Risk Score Is Associated With Intraocular Pressure and Improves Glaucoma Prediction in the UK Biobank Cohort - Gao, X. Raymond (Transl Vis Sci Technol, 2019)
PURPOSE: Elevated intraocular pressure (IOP) is an important risk factor for glaucoma. We constructed polygenic risk scores (PRSs) for IOP using the UK Biobank (UKB) data set to test whether the PRSs are associated with IOP and whether using them improves glaucoma prediction. METHODS: We conducted this study using 435,678 European participants from the UKB. We constructed weighted and unweighted PRSs using single nucleotide polymorphisms (SNPs) derived from the UKB data and previously reported IOP SNPs. We examined the associations of the PRSs with IOP and primary open-angle glaucoma (POAG) using linear and logistic regression, respectively. To quantify the discriminatory ability of the PRSs on POAG, we used the area under the receiver operating characteristic curve (AUC). RESULTS: The weighted PRS was significantly associated with IOP (P ∼ 10(−200)), after adjusting for age and sex. The PRS explained an additional 4% of variance in IOP. The weighted PRS was also significantly associated with POAG (P = 1.8 × 10(−77)). Subjects in the top quintile of the IOP PRS were 6.34 (95% confidence interval [CI]: 4.82–8.33; P = 2.1 × 10(−57)) times more likely to have POAG, compared to those in the bottom category. The weighted PRS improved the discriminatory power for POAG (AUC increased by 5%, P = 6.2 × 10(−22)) when added to the other covariates. The unweighted PRS exhibited similar results. CONCLUSIONS: We determined that IOP PRSs are significantly associated with IOP and improve the prediction of POAG. TRANSLATIONAL RELEVANCE: PRSs help reduce the burden of glaucoma by early detection of genetically susceptible individuals.